Physical, Laboratory, Radiographic, and Endoscopic Workup for Clostridium difficile Colitis - Baker, Samantha J.; Chu, Daniel I. (Clinics in Colon and Rectal Surgery, 2020)
Clostridium (reclassified as “Clostridioides”) difficile colitis is a common nosocomial infection associated with increased morbidity and mortality. Like many clinical encounters, a focused history and physical examination will help to guide initial management. Further laboratory testing will assist with diagnosis through stool studies, and blood tests, such as white blood cell counts and serum creatinine, can help to stratify patients into illness severity groups for treatment decisions. Radiographic evaluation can be helpful in patients with severe disease and concern for complicated colitis. Endoscopic evaluation should be carefully considered in patients with suspected mucosal injury secondary to infections and plays a role when an alternative diagnosis is suspected. Treatment options depend on the clinical presentation and can range from antibiotic therapy to emergent surgery to fecal transplantation for recurrent episodes. Care for these patients is often challenging, but through a systemic workup the appropriate treatment may be delivered.
Keywords: Clostridium difficile; C. difficile; pseudomembranous colitis; endoscopy